Victorian Society’s Hypocrisy and Its’ Impact to the Female Characters in George Bernard Shaw’s Mrs. Warren’s Profession - SITI NUR WAHYUNI (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2019)
Kemunafikan adalah salah satu persoalan sosial yang biasa terdapat dalam karya sastra. Masyarakat Victoria dalam drama Mrs. Warren’s Profession adalah termasuk masyarakat yang terkenal munafik. Penelitian ini difokuskan pada pengaruh kemunafikan masyarakat Victoria terhadap tokoh perempuan yang dimana mereka harus berjuang melawan kemunafikan masyarakat tempat mereka tinggal. Sumber data penelitian ini adalah drama karya George Bernard Shaw yang berjudul Mrs. Warren’s Profession. Data utama diambil dari sumber data yang mengimplikasikan kemunafikan masyarakat Victoria serta pengaruh dari kemunafikan terhadap tokoh perempuan. Data utama dianalisis bersama dengan data pendukung yang diambil dari buku-buku,kritik sastra, artikel, dan tulisan yang berkaitan. Peneliti menggunakan pendekatan sosiologi untuk mengetahui hubungan sosial dalam drama yang berkaitan dengan kemunafikan masyarakat Victoria. Penelitian kali ini akan mengemukakan dua permasalahan yang akan dibahas : 1. Bagaimana gambaran kemunafikan masyarakat era Victoria?. 2. Bagaimana kemunafikan masyarakat dapat mempengaruhi karakter perempuan dalam drama Mrs. Warren’s Profession?. Hasil dari penelitian ini menunjukan bahwa mayoritas masyarakat Victoria adalah munafik. Sosial status dan jabatan membuat mereka berusaha untuk terlihat baik namun kenyataannya tidak. Kemunafikan juga membuat Ny. Warren terjerumus dalam praktik rumah bordir. Dan putrinya Vivie, lebih percaya pada masyarakat daripada ibunya sendiri. Kata kunci : kemunafikan, masyarakat, Victoria, sosiologi, dramaturgi Hypocrisy is one of the social problems commonly found in literary works. The Victorian society in Mrs. Warren’s profession as well-known as hypocrite society. This research focused on Victorian society’s hypocrisy and its’ impact to the female characters who have to fight against the hypocrisy of the society where they live. The data source of this study was the play by George Bernard Shaw entitled Mrs. Warren’s Profession. The main data is taken from data sources which implies the hypocrisy of the Victorian’s society and its’ impact to the female characters. The main data were analyzed together with supporting data taken from books, literary criticism, articles and related articles. Researchers use a sociological approach to find out the social problems in the play that related to the hypocrisy of Victorian society. This study proposes two statement of the problem: 1. How is hypocrisy in Victorian society in Mrs. Warren’s Profession depicted?. 2. How the hypocrite society influence the female characters in Mrs. Warren’s Profession?. The results of this study indicate that Victorian’s society are hypocrites. Social status and position make them try to look good but the reality is not. The hypocrisy also makes Mrs. Warren fell into the brothel owner. And her daughter Vivie, prefer to trust in society where she belongs than her mother. Keywords : hypocrisy, society, Victoria, sociology, dramaturgy